Photovoltaic Technologies Perovskite Emerging Solar Cells - Deepak Choudhary (International Journal of Engineering and Management Research, 2019)
Photovoltaic solar cells are getting a lot of attention from all around the world because of their ability to produce electrical energy by harvesting photon energy, which is abundant and free on earth. However, the cost of electricity generation and the efficiency with which it is generated are critical factors. As a result, multiple solar cell generations have evolved in order to compete in the race for low cost and high efficiency. With the developing photovoltaic solar cell, Perovskite, it is possible to convert copious photon energy into electrical energy with high efficiency and low cost. The efficiency of perovskite solar cells, a new form of potential photovoltaic solar cell, increased rapidly from 3.8 in 2009 to 24.2 in 2019. Because of their high efficiencies, intrinsic flexibility, the variety of materials and synthetic processes that may be used to create them, and the different conceivable device topologies, PSCs have revolutionized photovoltaic research and development. Material compositions and device designs will be further optimized to improve efficiency and device stability. However, their stability is a key stumbling block to their commercialization.